The Effect of Perceived Organizational Support on Employee Engagement and Employee Performance - I Gusti Ngurah Bagus Arya Gemilang; I Gede Riana (Penerbit Kemala Indonesia, 2021)
This study is aimed to analyse the effect of perceived organizational support on work engagement and employee performance. This research was conducted by taking a saturated sampling of 49 respondents with a questionnaire tool created using google form. The structural equation modelling (SEM) analysis based on partial least square (PLS) is used as the data analysis technique. The results showed that perceived organizational support and employee engagement had a positive and significant effect on employee performance. Employee engagement considerably moderates the influence of perceived organizational support on employee performance. Based on the study's findings, management is expected to maintain the quality of human resources and employee welfare, pay attention to employee complaints, and retain employee pride in their work, so that the optimal contribution will be.